Tacit knowledge of auditors and their reflection on the effectiveness of the performance to some inspectors general offices - الكبيسي, صلاح الدين عواد; حسين, مصطفى خضير (Journal of Economics and Administrative Sciences, 2017)
This research aims to find out the extent the reflection of tacit knowledge dimensions (experience, skill, intuition, the ability to think) on Organizational performance of the offices of inspectors general dimensions (internal processes, growth and learning the focus, the focus on the customer) and the measurement and analysis of the type of impact the tacit knowledge of auditors on performance Organizational in inspectors general offices, the research seeks to diagnose the extent of awareness of Office Management knowledge implicit and the attention span of the administration in determining levels and performance levels, and the resolution means the main information-gathering adopted by the researcher, which, as well as his experience through his work in the Office of the Inspector General and conduct some interviews and the collection of quantitative data for activities and events of some offices and for (5) years, has been chosen deliberately, a sample of (57) individuals degree inspector general and deputy inspector general and director of the censorship department, auditing, and was chosen this sample because they are the direct beneficiaries of the auditors' reports, were use a lot of statistical methods، The researcher found that the number of results, most notably the tacit knowledge of auditors affect the achievement of the effectiveness of the performance of some of the offices of inspectors general.